2013
DOI: 10.13005/ojc/290343
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Leaching of Heavy Metals from E-waste

Abstract: The electronic revolution is certainly a boon to mankind but at the same time, the use and throw culture and the greed of the human race to adopt new technologies have resulted in the generation of wastage of unwanted, discarded or broken electrical or electronic appliances, which is called e-waste. The rate at which e-waste mounts up has become a global concern. In the present scenario, the used electronic and electrical equipment reach the unorganized sectors where

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…E-waste is not hazardous waste by itself, but some components of e-waste can be harmful. 7 E-waste may be comprised of rubber, glass, ceramics, ferrous and non-ferrous metals, plastics, printed circuit boards and other items. Iron and steel make up a large quantity of e-waste, followed by plastics, non-ferrous metals and other components.…”
Section: Introductionmentioning
confidence: 99%
“…E-waste is not hazardous waste by itself, but some components of e-waste can be harmful. 7 E-waste may be comprised of rubber, glass, ceramics, ferrous and non-ferrous metals, plastics, printed circuit boards and other items. Iron and steel make up a large quantity of e-waste, followed by plastics, non-ferrous metals and other components.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of those two extractants has been made by Rout et al in 2011 particularly on Americium and Europium [8][9] . This study showed extraordinary power of extraction for these metals…”
Section: D2ehpa-hdehdgamentioning
confidence: 99%
“…The effects of parameters such as aqueous to organic phase's volume ratio, metal concentration IL concentration, pH levels, ionic strength, and temperature were reported 10 . …”
Section: D2ehpa -C 4 Mimmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to determine the species of arsenic in food because of their high toxicity. Various instrumental techniques, such as flame atomic absorption spectrometry (FAAS) 6 , inductively coupled plasma-optical emission spectrometry (ICP-OES) 7,8 , inductively coupled plasma-mass spectrometry (ICP-MS) 9 ,flow injectionhydride generation atomic absorption spectrometric (FI-HGAAS) 10 , UV-Vis spectrop-hotometry 11 , voltammetric method 12 and colorimetry incorporated with image processing 13 have been used to accurately and precisely determine As at trace levels in various samples.…”
Section: Introductionmentioning
confidence: 99%